2007
DOI: 10.1258/002367707779399428
|View full text |Cite
|
Sign up to set email alerts
|

How isoflavone levels in common rodent diets can interfere with the value of animal models and with experimental results

Abstract: SummaryPhytoestrogens are a diverse group of plant-derived compounds structurally or functionally mimicking mammalian oestrogens. A variety of effects, in vitro, in animal models and in humans, have been attributed to these compounds. It is generally not appreciated that many commercial rodent diets are formulated with soy as a source of protein and thus large daily doses of phytoestrogens in the form of isoflavones are delivered to the animals. The content of isoflavones in laboratory diets depends on a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 49 publications
2
64
0
Order By: Relevance
“…This dietary manipulation can be a useful tool to study food allergy in mouse strains that are amenable for genetic manipulations. Batch-to-batch variations in isoflavone content in rodent diets [2,3,7] may contribute to fluctuations in the experimental data, especially those involving the immune system. Therefore, it is important to check and control the isoflavone content in rodent diet formulations when designing animal experiments to obtain reliable and reproducible experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This dietary manipulation can be a useful tool to study food allergy in mouse strains that are amenable for genetic manipulations. Batch-to-batch variations in isoflavone content in rodent diets [2,3,7] may contribute to fluctuations in the experimental data, especially those involving the immune system. Therefore, it is important to check and control the isoflavone content in rodent diet formulations when designing animal experiments to obtain reliable and reproducible experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, soybeans are an abundant source of immune-modulatory and phytoestrogenic compounds called isoflavones. Several reports show the impact of dietary isoflavones on various aspects of animal research [1,2,3,4,5]. Circulating isoflavone levels are an important factor in research involving animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to diet, many laboratory animal feeds exhibit oestrogenic activity (6,15,31). It was found that soy isoflavones present in feed at high amounts interfere with the value of animal models and with experimental results (10). An example of this was a decreased sensitivity of immature rats (5) and hamsters (20) in the uterotrophic bioassay.…”
Section: Discussionmentioning
confidence: 99%
“…These assays are also applicable for testing dietary compounds either as single ingredients, mixtures, or as a part of diet. However, the assays are often confounded by the presence of bioactive compounds in the diet (13).…”
Section: Introductionmentioning
confidence: 99%